HUBUNGAN STATUS SOSIAL EKONOMI KELUARGA DAN KONSUMSI ZAT GIZI DENGAN STATUS GIZI ANAK DI SD NEGERI 094118 DESA MARUBUN LOKKUNG KECAMATAN DOLOK SILAU KABUPATEN SIMALUNGUN TAHUN 2015 - Meyanta Sinaga; Evawany Y Aritonang; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
School-age children during growth and development often experience nutritional problems. Nutritional problems, especially malnutrition can inhibit the growth and development of school-age children. Optimal nutrition is necessary in school age children, because the impact is directly related to the achievement of qualified human resources.This study aimed to determine the relationship of the socioeconomic status of families and food intake of children with the nutritional status of elementary school children in SD Negeri 094118 Marubun Lokkung Kecamatan Dolok Silau Kabupaten Simalungun 2015. This reasearch use analitic observation method with cross sectional approach. The instrument used in this research are: 1. Scales, 2.Food Recall 2x24 hours. The technique of taking data is done through observation, interview, and documentation. The analysis of the research’s result done through chi square test.From the research result it is found that family’s income has related significant with children’s nutrition status (p=0.000). Where as the other variable such as parent’s education level, family’s members and child food intake have no meaningful relationship with children’s nutritional status (p>0,05). It is recommended that the school considers the shape and target of health and nutrition programs in improving the nutritional status of primary school and parents to pay more attention to their child's diet.Keywords: Socioeconomic Status, food intake, Nutritional Status, elementary school children